2012
DOI: 10.1016/j.surfcoat.2011.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microstructural characterization of (Y or Zr)-doped CrAlN coatings

Abstract: Magnetron sputtered chromium aluminium nitride films are excellent candidates for advanced machining and protection for high temperature applications. In this work CrAlNbased coatings including Y or Zr as dopants (2 at. %) are deposited by d.c. reactive magnetron sputtering on silicon substrates using metallic targets and Ar/N 2 mixtures. The hardness properties are found in the range of 22-33 GPa with H/E ratios close to 0.1. The influence of the dopant element in terms of oxidation resistance after heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…1. The CrAlYN-A and CrAlYN-B coatings present a typical columnar structure similar to that observed by the pure CrAlN in our previous publication [13]. A multilayer structure can be clearly seen in the inset images at higher magnification.…”
Section: Chemical and Microstructural Characterizationsupporting
confidence: 83%
See 2 more Smart Citations
“…1. The CrAlYN-A and CrAlYN-B coatings present a typical columnar structure similar to that observed by the pure CrAlN in our previous publication [13]. A multilayer structure can be clearly seen in the inset images at higher magnification.…”
Section: Chemical and Microstructural Characterizationsupporting
confidence: 83%
“…In a previous work, we demonstrated that yttrium (1.7 at.%) was better than zirconium to increase the oxidation resistance of CrAlN coatings deposited on silicon at 1000 • C in air with Al contents below 10 at.% [13], although zirconium was better to reduce friction [4]. Moreover, the protectiveness of nanostructured CrAlYN coatings [∼4-12 at.% of Al; ∼2-5 at.% of Y] deposited on P92 steel against steam oxidation at 650 • C was found to be comparable to conventional microstructured aluminides at much lower thickness than used for steam turbine components [21,22] the location of the metallic elements inside ternary or quaternary nitrides and their chemical state may have a significant influence on the oxidation behavior and protective mechanism.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the addition of a reactive element was suggested to reduce the accumulation of voids at the substrate/scale interface [21]; to improve the mechanical properties of the scale by modifying its structure [22] or to prevent the grain coarsening at elevated temperatures [23]. In a previous work we also confirmed the improved oxidation resistance of a CrAlYN coating in comparison to CrAlZrN [24]. The tribological properties of CrAlN coatings have been investigated previously [6,7,[25][26][27] but only limited information is available about their tribological behavior at high temperature [28][29][30].…”
Section: Introductionsupporting
confidence: 71%
“…In order to improve their behaviour, additional elements have been included in their composition such as Al, Ti, Nb and rare earths as Y or Zr [10][11][12]. Following other approach different arrangements of the coating multilayers have been also tested exploring the effect of alternating layers with thickness and composition variations [13][14][15].…”
Section: Introductionmentioning
confidence: 99%